Designing an immersive visit for public space assessment - Issa, Elie; Belaroussi, Rachid (Edelweiss Applied Science and Technology, 2024)
The assessment of the quality of public spaces is crucial for fostering community well-being and urban development, contributing to the creation of inclusive, vibrant, and sustainable urban environments. It is possible to forecast the feeling imprinted in people by a future streetscape using virtual reality. Immersive visits are the best technological solution, given that a virtual environment of quality is provided with high quality resolution and urban details. The Architecture, Engineering, and Construction (AEC) professionals involved in a large-scale real estate project under construction provided us with access to the BIM (Building Information Model) architectural plans of the entire infrastructure in the future district. A part of the neighborhood has already been built and is studied in this experiment: a public place with a tram station, a typical shopping street, and a pedestrian way, mainly a public place for leisure activity. These three points of view of interest will be studied with two modalities: real video showing the actual state of the built environment, and immersive visits using head-mounted devices, enabling virtual reality exploration of these public places. This article explains the practical construction of the 3D city model, and characterize the quality of the immersive visits through the use of questionnaires submitted to laypersons (non-expert participants).